(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
This paper explores the concept of mediaethics with special reference to the Indian news media. In India media ethicshave been a convention associated with the traditional mass media. But with thedevelopment in technology and the advent of the internet the standard ethicalpractices are facing continuous challenge. This paper discusses three incidentswhere the traditional mass media - the press or television - deviated from theestablished ethical principles and journalistic norms normally practiced by theIndian news media. This paper will explore those aberrations and analyze theethical principles of the news media that has been manipulated for a moreworldly purpose. The paper draws conclusion on the future of media ethics inthe context of Indian news media.